Towards a theory of mime - Iliev, Aleksander 1956- (Routledge, 2014)
"Towards a Theory of Mime is a genuinely unique book about non-verbal communication and performance. Combining a broad global history of the evolution of human communication with an introduction to the general practice of mime, Alexander Iliev traces a lineage from Marceau and Barrault to his own distinguished practice as performer and teacher. The book moves from a fascinating description of the first principles of gestural language to a stunning sequence of specific exercises in practical training. Written in a sometimes poetic, always accessible and often humorous style, Towards a Theory of Mime conveys complex ideas in a strikingly accessible way"--Provided by publisher.